The Suitability Of Readibility Levels Of Reading Texts In English Textbook For Tenth Grader By Kemendikbud - Kurniati, Dewi; Simaibang, Baginda; Mulyadi, Mulyadi (Jurnal Pendidikan Tambusai, 2021)
This research aimed at finding the suitabality of the readability levels of reading texts in English textbook entitled Bahasa Inggris Kelas X which is used at the tenth grade students of IBA Senior High School. There are ten reading texts in textbook, they met calculated by using The Dale-Chall Formula and Cloze Procedure Test to know about the suitabality and readability levels of reading texts. From this research there are only two reading texts in English textbook Entitled Bahasa Inggris Kelas X by Kemendikbud are suitable for tenth grade students and they were classified into Independent Level, it means that the reading texts considered easy enough for students to read on their own without any help. In conclusion that readability of reading materials in the textbook is found reading materials in the textbook is found reading m suggest that readability of reading materials are suitable with students grade level.